BMP-2 and BMP-7 affect human rotator cuff tendon cells in vitro - Pauly, Stephan; Schmidmaier, Gerhard (Journal of shoulder and elbow surgery, 2012)
Background Rotator cuff repair is prone to incomplete regeneration. To explore biological improvements of tendon-bone healing, it was the aim of this study to investigate the influence of growth factors bone morphogenetic protein (BMP)-2 and BMP-7 on tenocyte cell activity and matrix gene expression and production. A beneficial effect of these factors would be promising to improve tendon-bone healing in vivo. Methods Tenocyte-like cells were isolated from human rotator cuff tissue samples (supraspinatus and long head of biceps tendon) and incubated with BMP-2 (100-1000 ng/mL) and BMP-7 (100-2000 ng/mL), both alone and in combination. At days 0, 3, and 6, cell activity was assessed. At day 6, collagen type I production and the expression of several tendon-, bone-, and cartilage-related markers (collagen types I-III, osteocalcin, scleraxis) were evaluated. Results Dose-dependent effects of both investigated growth factors on tenocyte-like cells were observed. Application of BMP-2 increased collagen type I production significantly but its expression only slightly. Cell activity was decreased in higher doses over time. For BMP-7, a significant increase in collagen type I production and expression, as well as increased cell activity, was observed. The addition of both factors resulted in decreased parameters when compared with BMP-7 alone. The expression of collagen types II and III, osteocalcin, and scleraxis was not significantly affected by application of BMPs. Conclusion Besides the well-known effects of BMP-2 and BMP-7 on osteoblasts, this study describes further effects on rotator cuff tendon cell biology. Both tissue types potentially need to be addressed to improve tendon-bone healing of the rotator cuff.